Cultural Heritage And Its Historical Perception: Analysis from antiquity to the present - Calderón Puerta, Diego Manuel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Cultural heritage as an intrinsic element of human activity has undergone notable changes in its perception depending on the historical context in which it is generated. That is why, approaching the role it has played over time, is essential to understand its situation and determine the challenges it faces. The objective of this article is, on the one hand, to analyze the historical evolution of the perception of cultural heritage and, on the other, to reflect on the role it plays in contemporary society.